Volume 7B: Structures and Dynamics 2015
DOI: 10.1115/gt2015-43628
|View full text |Cite
|
Sign up to set email alerts
|

Self-Excited Blade Vibration Experimentally Investigated in Transonic Compressors: Rotating Instabilities and Flutter

Abstract: This paper investigates the vibrations that occurred on the blisk rotor of a 1.5-stage transonic research compressor designed for aerodynamic performance validation and tested in various configurations at Technische Universität Darmstadt. During the experimental test campaign self-excited blade vibrations were found near the aerodynamic stability limit of the compressor. The vibration was identified as flutter of the first torsion mode and occurred at design speed as well as in the part-speed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…This type of interaction has been reported in recent experimental and computational investigations such as Kielb et al (2003), Dodds (2016) and Holzinger et al (2016). As blades in multi-stage compressors become more loaded, the occurrence of such events is expected to be frequent.…”
Section: Introductionsupporting
confidence: 53%
“…This type of interaction has been reported in recent experimental and computational investigations such as Kielb et al (2003), Dodds (2016) and Holzinger et al (2016). As blades in multi-stage compressors become more loaded, the occurrence of such events is expected to be frequent.…”
Section: Introductionsupporting
confidence: 53%
“…1. The geometry as commissioned in the FUTURE project was designed to encounter flutter in the operating range, and non-synchronous excitations were observed [2]. The here presented focus is on the encountered resonance crossing of the first rotor torsion mode (1T) in the operating range of the compressor.…”
Section: Test Rigmentioning
confidence: 99%
“…Their study suggests that the RIs are due to synchronized tip clearance vortex oscillation across the blade passages. Holzinger et al 12 conducted experimental investigations on a 1.5-stage transonic research compressor. They found that RIs occur as the tip clearance is enlarged, and then develop into self-excited vibration of critical amplitude.…”
Section: Introductionmentioning
confidence: 99%